Cost-effectiveness of internal limiting membrane peeling versus no peeling for patients with an idiopathic full-thickness macular hole: results from a randomised controlled trial. Issue 3 (6th September 2011) - Ternent, Laura; Vale, Luke; Boachie, Charles; Burr, Jennifer M; Lois, Noemi; ,
Abstract : Aim: To determine whether internal limiting membrane (ILM) peeling is cost-effective compared with no peeling for patients with an idiopathic stage 2 or 3 full-thickness macular hole. Methods: A cost-effectiveness analysis was performed alongside a randomised controlled trial. 141 participants were randomly allocated to receive macular-hole surgery, with either ILM peeling or no peeling. Health-service resource use, costs and quality of life were calculated for each participant. The incremental cost per quality-adjusted life year (QALY) gained was calculated at 6 months. Results: At 6 months, the total costs were on average higher (£424, 95% CI −182 to 1045) in the No Peel arm, primarily owing to the higher reoperation rate in the No Peel arm. The mean additional QALYs from ILM peel at 6 months were 0.002 (95% CI 0.01 to 0.013), adjusting for baseline EQ-5D and other minimisation factors. A mean incremental cost per QALY was not computed, as Peeling was on average less costly and slightly more effective. A stochastic analysis suggested that there was more than a 90% probability that Peeling would be cost-effective at a willingness-to-pay threshold of £20 000 per QALY. Conclusion: Although there is no evidence of a statistically significant difference in either costs or QALYs between macular hole surgery with or without ILM peeling, the balance of probabilities is that ILM Peeling is likely to be a cost-effective option for the treatment of macular holes. Further long-term follow-up data are needed to confirm these findings.